The Effect of Work-Based Learning on the Acquisition of Technical Skills amongst Mechanical Engineering Students in National Polytechnics in Western Kenya Region - Migiro L. , Wycliffe; Kisilu, Kitainge; Dimo , Herbert (African Journal of Education,Science and Technology (AJEST), 2022)
The right approach to teaching and evaluation of practical subjects in technical colleges is crucial in imparting practical skills and adequate creative power to students in order to meet the requisite human resource skills needed in achieving Sustainable Development Goals (SDGs 2016-2030), through Technical and Vocational Education and Training (TVET). Teaching methods can affect acquisition of technical skills by mechanical engineering students in national polytechnics. The study determined the effect of work-based learning on acquisition for mechanical engineering students in national polytechnics in Western Kenya Region. An explanatory research design was used and random samples was used to sample mechanical engineering trainees (248) and trainers (66) in 3 (Kisii, Kisumu, Sigalagala) national polytechnics in western Kenyan region. Data was collected using structured questionnaires which were selfadministered. Data was analyzed by use of both inferential and descriptive statistics using SPSS version 25.0. Results of multiple regressions revealed that work-based learning affected acquisition of technical skills in mechanical engineering in national polytechnics. There was a positive significant effect of 67.1% in acquisition of technical skills with a beta value of 0.178 for work-based learning. The findings imply that national polytechnics should embrace a worked based learning methods complemented by other approaches such as virtual learning and computer aided learning and proactively formulate policies and resources which support the teaching methods above in order to improve acquisition of technical skills among mechanical engineering students.